The Transatlantic Trade and Investment Partnership: exaggerated hopes from the liberalising agenda? - Myant, Martin (Brussels, 2014)
"This policy brief provides evidence that the economic benefits of the Transatlantic Trade and Investment Partnership (TTIP) have been seriously exaggerated. It also provides some ideas for an alternative globalisation agenda which would enshrine higher labour and environmental standards into trade negotiations."